Device-Based Treatment in Hypertension: At the Forefront of Renal Denervation. Issue 2 (8th June 2021) - Kario, Kazuomi; Hettrick, Douglas A.; Esler, Murray D.
Abstract : Abstract: Percutaneous renal denervation is a novel device therapy that modifies the circulatory regulatory system and has received considerable attention recently. This treatment partially blocks the renal sympathetic nervous system, which is an organ-connecting pathway between the brain and the kidney. Denervation techniques currently under clinical investigation include radiofrequency, ultrasonic, and chemical ablation with alcohol, all of which are executed through transcatheter access to the renal artery. All recently published randomized sham-controlled trials have shown a clear antihypertensive effect of renal denervation over 24 hours, including during the nighttime and early morning. This treatment has promise in the management of poorly controlled hypertension as well as in the prevention of the development or aggravation of arrhythmias and heart failure.